2004
DOI: 10.1094/phyto.2004.94.6.578
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster of Major Specific Resistance Genes to Leptosphaeria maculans in Brassica napus

Abstract: Two types of genetic resistance to Leptosphaeria maculans usually are distinguished in Brassica napus: qualitative, total resistance expressed at the seedling stage and quantitative, partial resistance expressed at the adult plant stage. The latter is under the control of many genetic factors that have been mapped through quantitative trait loci (QTL) studies using 'Darmor' resistance. The former usually is ascribed to race-specific resistance controlled by single resistance to L. maculans (Rlm) genes. Three B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
169
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(175 citation statements)
references
References 30 publications
6
169
0
Order By: Relevance
“…Classical and molecular genetic studies on a wide array of plant-pathogen systems have demonstrated that R loci can be single genes with multiple alleles (like the 13 alleles for the L locus in flax) or, more commonly, clusters of genes that can affect resistance to different pathogens (reviewed in Michelmore and Meyers 1998). A similar close relationship has been suggested in earlier reports between cotyledon resistance genes from Shiralee and Maluka (Mayerhofer et al 1997), between those from Maluka and RB87-62 (Rimmer et al 1999), and between the resistance genes Rlm3, Rlm4, Rlm7, and Rlm9 present in the B. napus lines Maxol, Quinta, 23.1.1., and Darmor, respectively (Delourme et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Classical and molecular genetic studies on a wide array of plant-pathogen systems have demonstrated that R loci can be single genes with multiple alleles (like the 13 alleles for the L locus in flax) or, more commonly, clusters of genes that can affect resistance to different pathogens (reviewed in Michelmore and Meyers 1998). A similar close relationship has been suggested in earlier reports between cotyledon resistance genes from Shiralee and Maluka (Mayerhofer et al 1997), between those from Maluka and RB87-62 (Rimmer et al 1999), and between the resistance genes Rlm3, Rlm4, Rlm7, and Rlm9 present in the B. napus lines Maxol, Quinta, 23.1.1., and Darmor, respectively (Delourme et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Closely linked loci for adult and seedling resistance were identified in the canola cultivar Major and in the B. napus breeding accessions RB87-62 and DH88-752 (Ferreira et al 1995;Zhu and Rimmer 2003). Similarly, the race-specific cotyledon resistance gene Rlm1 has been shown to explain 70% of the variation for adult plant resistance in the French cultivar Maxol (Delourme et al 2004). In fact, the strong correlation between seedling and field resistance in the Australian canola cultivar Maluka was exploited to expedite the development of the cultivar Quantum for Western Canadian field conditions (Stringam et al 1995).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Avr gene clustering in L. maculans and a counterpart clustering of R genes in B. napus (Delourme et al, 2004).…”
Section: Molecular Interaction Between Brassica and L Maculansmentioning
confidence: 98%